Pemberdayaan Masyarakat Melalui Edukasi K3 Rumah Tangga dan Tanaman Hidroponik untuk Ketahanan Pangan di Desa Kota Baru Kabupaten Muara Enim - Annisah Biancika Jasmine; Ajeng Dwiratu Qaida Maharani; Rehsa Apriliana; Sakira Septy Wahyuningsih; Irren Jetty Nuranisa; Vanya Gita Purnamasari; Helen Enjelia; Adethya Amirah Azaria; Siti Hawa Dewi Utari; A. Sekar Arum Widhiastuti; Arviana Pridamayanti; M. Yusuf Habibi (Departement of Environmental Health, Faculty of Public Health, Sriwijaya University, 2026)
Food security is a crucial issue that significantly impacts the quality of life, particularly in rural areas that continue to face food insecurity due to limitations in technology, infrastructure, and market access. Furthermore, the implementation of occupational safety and health within households is a critical aspect in preventing the risk of domestic accidents and illnesses. This community service activity was conducted in Kota Baru Village, Lubai Subdistrict, Muara Enim Regency, targeting housewives, with the aim of improving community understanding related to household OSH and food security. The implementation methods included interactive lectures and hands-on practice, involving training in hydroponic cultivation using recycled materials, as well as educational sessions on household occupational safety and health. The activity was evaluated using pre-test and post-test questionnaires administered to the respondents. The results showed an increase in the average score of household OSH knowledge from 75.38 to 88.00 among 40 respondents, and an increase in food security knowledge from 85.00 to 97.00 among 20 respondents. The Wilcoxon test revealed significance values of 0.000 and 0.001, respectively, indicating statistically significant improvements. This program has proven to be effective in enhancing community understanding, as evidenced by the substantial improvement in knowledge after the intervention. For future community service efforts, it is recommended to develop relevant programs with more regular implementation to ensure sustained benefits for the community.